Urgensi Pengaturan Pertanian Perkotaan Berkelanjutan Berbasis Perubahan Iklim - Listiningrum, Prischa; Magistra, Muhammad Reza (PROGRESIF: Jurnal Hukum, 2023)
This paper examines regulations concerning climate change mitigation and adaptation efforts in the agricultural sector. A doctrinal method is applied to unpack the authority of the central and regional governments in realizing sustainable agriculture at the urban level, especially in the city of Blitar, where agriculture has been negatively affected due to the changes in weather. This research found that Indonesia already has Law Number 22 of 2019 concerning the Sustainable Agricultural Cultivation System, which contains 35 provisions mandating further regulations at the regional levels. Nevertheless, not all regions, including the Blitar City, have carried out this mandate.